Technology Readiness and Artificial Intelligence Adoption by Accounting and Finance Students in Tunisia - Charfi, Souha; Mallouli, Yosra (Archives of Business Research, 2025)
Highlighting the fundamental role of universities in preparing future accountants and financiers for an economy characterized by AI technologies progress, this study examines the relationship between accounting and finance students’ technological readiness and their decision to adopt AI technologies by demonstrating the mediating effect of perceptions of use on this relationship, in the context of a developing country, Tunisia. Based on the Technology Readiness of Acceptance Model (TRAM), we designed a comprehensive survey to collect information on perceived use (PU), perceived ease of use (PEOU), technology readiness (TR), and technology adoption (TA). A total of 125 accounting and finance students from a public university in Tunisia were selected. Statistical analysis based on regressions, were performed using SPSS 25. The findings revealed the positive impact of PU, PEOU, and TR on TA. Furthermore, statistical analysis showed the mediating role of PEOU and PU on the relationship between TR and AI adoption by Tunisian students. This study contributes to the limited literature that investigates the drivers of AI adoption by accounting and finance students. Furthermore, this study confirms that the measurement scales used by the literature to measure TA, and its determinants are valid and reliable in developing countries such as Tunisia.